2012
DOI: 10.1007/s00216-012-6476-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of miRNA-222 by use of a magnetic bead-based bioassay

Abstract: MicroRNAs (miRNAs, miRs) are naturally occurring small RNAs (approximately 22 nucleotides in length) that have critical functions in a variety of biological processes, including tumorigenesis. They are an important target for detection technology for future medical diagnostics. In this paper we report an electrochemical method for miRNA detection based on paramagnetic beads and enzyme amplification. In particular, miR 222 was chosen as model sequence, because of its involvement in brain, lung, and liver cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 42 publications
4
65
0
Order By: Relevance
“…In the previous years, researchers have been challenged to push the sensitivity of analytical bioassays down to subnanomolar values while keeping these procedures as simple, reliable, and cost-effective as possible. In particular, the formation of supramolecular assemblies and the use of enzymes to enhance the sensitivity of genoassays have been the subject of many research efforts [ 6 ] [ 7 , 8 ]. Outstandingly low detection limits were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous years, researchers have been challenged to push the sensitivity of analytical bioassays down to subnanomolar values while keeping these procedures as simple, reliable, and cost-effective as possible. In particular, the formation of supramolecular assemblies and the use of enzymes to enhance the sensitivity of genoassays have been the subject of many research efforts [ 6 ] [ 7 , 8 ]. Outstandingly low detection limits were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Previously magnetic beads have been used as immobilization surface for various components of complex biological reactions on microfluidic chips [18][19][20][21][22]; however, their use as a label has been explored in many studies. Use of magnetic beads as a label for immunoassays is, indeed, better as it avoids reaction with various chemical tags, which further reduces the assay time and increases sensitivity of the measurement system.…”
Section: Introductionmentioning
confidence: 99%
“…This renders miRNAs promising candidates not only as cancer biomarkers, but also as potential therapeutic targets. Simple and inexpensive methods are currently being developed for their sensitive detection not only in tissues, but ideally in body fluids such as blood, urine or saliva, including methods based on electrochemical (EC) detection [3][4][5][6][7].Recently, we have reported that miRNAs can be easily and quickly labeled with electroactive osmium(VI)-based complexes [8]. In the first step, we took an advantage of high kinetics of reaction between terminal ribose at the 3'-end and Os(VI)py, followed by an exchange of pyridine (py) for 2,2'-bipyridine (bipy) to achieve higher stability of the adducts, more convenient for the EC analysis.…”
mentioning
confidence: 99%